ผลกระทบที่อาจเกิดขึ้นจากการประยุกต์ (ร่าง) มาตรฐานการบัญชีการเกษตรสำหรับธุรกิจฟาร์มสุกรในประเทศไทย - สุรีย์ ภิญโญวรคุณ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
To know the current accounting practice related to biological assets and agricultural production of swine farming companies, to know and analyze the effects of applying the exposure draft of Thai accounting standard on agriculture accounting in according to the possible problems and benefits including the recommendation, and to analyze the effects to the financial statement in case study of the company which applies the exposure draft. The research methodology is a descriptive and survey research. The primary data is collected from accountants, auditors and swine specialists. The secondary data is collected from the related academic documents. The study is focused on the possible problems which are the measurement problem under fair value for biological assets, the disclosure problem and other related problems. The research result is found that the current accounting practices are to recognize and measure the value of inventory (swine) under the historical cost. The parent stocks are valued at historical cost less accumulated depreciation. The valuation problem for biological assets is that the companies are unable to identify the reliable market value for the swine products which are not available for sale. The disclosure problem is that the companies cannot disclose some of the secret information. The other problems are the conflict of accounting practice between the exposure draft and revenue department, the complication in preparing financial statement and so on. The recommendation for the measurement problem is that the companies may follow the allowed alternative treatments. Furthermore, the training course is necessary for accountants, auditors and others who are interesting and involving in the agriculture accounting standard in order to educate people to know the practical accounting standard of agriculture.